ANALISIS TINGKAT KESESUAIAN WISATA BAHARI PADA EKOSISTEM TERUMBU KARANG DI PULAU LAREA- REA KABUPATEN SINJAI - Isra Wahyudi; Asbar Asbar; Danial Danial (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2021)
This study aims to determine the potential and percentage of coral reef cover, know the tourism suitability index and environmental carrying capacity, know the direction of coral reef ecosystem management. The research method is using UPT (Underwater Photo Transect), as well as measurement of environmental parameters on Larea-rea Island. Data analysis using CPCe 4.1 software, and Arcgis 10.8. Than, an analysis of the suitability of diving tourism and an analysis of the carrying capacity of the area is carried out (Yulianda, 2018).The results of this study indicate that the percentage of potential coral reef cover at all stations is 10-36%, indicating that the coral condition is not good (according to the conditions). The number of lifeform types ranged from 8-12, while the number of fish species obtained was 37-44 species. The suitability class category based on the results of the analysis at the three stations obtained the appropriate category (S2), with a percentage of the IKW value of 50-67%. Then, area carrying capacity (DDK) in the diving tourism category is an average of 528 people / day from the three stations.Management and development of marine tourism can be done by determining the zone of utilization and rehabilitation of coral reef ecosystems, as well as limiting visitors for certain periods to reduce the potential impact of environmental degradation.